Designing Passive Harmonic Filter of Electric Propulsion System on Tanker Ship - Indra Ranu Kusuma; Semin; Muhammad Badrus Zaman; Faisal Muhammad Satrio (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2018)
Harmonic is a frequency defect that have some negative effect to the electrical network system. In a ship, electrical network system are interconnected to each other to another electrical consumer device. The effect will impact all the device that connected to the electrical network system. This can be reducing the consumer devices reliability. This research analyzed and simulate the effect of harmonic when there is no harmonic filter condition and with a passive harmonic filter for each operating condition on this ship. This research also includes the comparison diagram between no filter and with a passive harmonic filter condition, and some simulation report from the software. The research results were VTHD value are need to be comply with the classification standards and rules. Passive harmonic filter can reduce the VTHD value by reducing a specific harmonic order and the impact from reducing specific harmonic order can reduce the other harmonic order. Besides that, passive harmonic filter also can gain a higher power factor (PF) value.